Case Report: Decompressive Craniectomy for COVID-19 Malignant Cerebral Artery Infarction. Is Surgery a Good Option? - Sáez-Alegre, Miguel; García-Feijoo, Pablo; Millán, Pablo; Vivancos Sánchez, Catalina; Rodríguez Domínguez, Víctor; García Nerín, Jorge; Isla Guerrero, Alberto; Gandía-González, María Luisa (Frontiers in Neurology, 2021)
SARS-CoV2 infection can lead to a prothrombotic state. Large vessel occlusion, as well as malignant cerebral stroke have been described in COVID-19 patients. In the following months, given the increase in COVID-19 cases, an increase in malignant cerebral SARS-CoV2 associated strokes are expected. The baseline situation of the patients as well as the risk of evolution to a serious disease due to the virus, depict a unique scenario. Decompressive craniectomy is a life-saving procedure indicated in patients who suffer a malignant cerebral stroke; however, it is unclear whether the same eligibility criteria should be used for patients with COVID-19. To our knowledge seven cases of decompressive craniectomy and malignant cerebral stroke have been described to date. We report on a 39-year-old female with no major risk factors for cerebrovascular disease, apart from oral contraception, and mild COVID-19 symptoms who suffered from left hemispheric syndrome. The patient underwent endovascular treatment with stenting and afterward decompressive craniectomy due to a worsening neurological status with unilateral unreactive mydriasis. We present the case and provide a comprehensive review of the available literature related to the surgical treatment for COVID-19 associated malignant strokes, to establish whether the same eligibility criteria for non-COVID-19 associated strokes should be used. Eight patients, including our case, were surgically managed due to malignant cerebral stroke. Seven of these patients received decompressive craniectomy, and six of them met the eligibility criteria of the current stroke guidelines. The mortality rate was 33%, similar to that described in non-COVID-19 cases. Two patients had a left middle cerebral artery (MCA) and both survived after decompressive craniectomy. Our results support that decompressive craniectomy, using the current stroke guidelines, should be considered an effective life-saving treatment for COVID-19-related malignant cerebral strokes.